Bandwidth Enhancement of a Multilayered Polymeric Comb Array Antenna for Millimeter-Wave Applications - Wan Asilah, Wan Muhamad; Razali, Ngah; Mohd Faizal, Jamlos; Ping, Jack Soh; Mohd Tarmizi, Ali; Narbudowicz, Adam (Springer Berlin Heidelberg, 2017)
This paper introduces a new multilayered polymeric comb array antenna fabricated on a polydimethylsiloxane (PDMS) dielectric substrate. PDMS is selected due to its excellent electrical and mechanical properties such as low permittivity, water resistance and robustness. The polymeric comb array antenna consists of a zigzag array aligned at −90° with respect to the radiating patch with full ground plane. The radiating patch is embedded inside the PDMS substrate while the coaxial connector is located at the bottom of the transmission line. The proposed antenna functions from 22.649 to 27.792 GHz. Simulated and measured reflection coefficients and radiation patterns agreed well. A maximum gain of 9.856 dB is recorded at 25 GHz, indicating suitability for implementation in millimeter-wave applications.